2021
DOI: 10.1016/j.jafrearsci.2021.104226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and projection of mean surface temperature using CMIP6 models over East Africa

Abstract: This study evaluates the historical mean surface temperature (hereafter T2m) and examines how T2m changes over East Africa (EA) in the 21 st century using CMIP6 models. An evaluation was conducted based on mean state, trends, and statistical metrics (Bias, Correlation Coefficient, Root Mean Square Difference, and Taylor skill score). For future projections over EA, five best performing CMIP6 models (based on their performance ranking in historical mean temperature

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 123 publications
1
26
0
Order By: Relevance
“…Projected changes in PRCPTOT and CWD signifying an increase in mean seasonal precipitation and more wet days will likely be of great benefit to the various sectors that support the economy of the region (Figures 2 and 3). For instance, the projected decline in PRCPTOT over southern parts of Tanzania under SSP2-4.5 scenario will have catastrophic impact on the ecosystem and the livelihoods of people who continue to face the impact of abrupt declines in seasonal precipitation leading to drought episodes since 1990s [32,34,45,46,76]. Meanwhile, R95 p shows large uncertainties over the study area during MAM season as compared to other indices, with larger interquartile model spread exhibited (Figure 4).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Projected changes in PRCPTOT and CWD signifying an increase in mean seasonal precipitation and more wet days will likely be of great benefit to the various sectors that support the economy of the region (Figures 2 and 3). For instance, the projected decline in PRCPTOT over southern parts of Tanzania under SSP2-4.5 scenario will have catastrophic impact on the ecosystem and the livelihoods of people who continue to face the impact of abrupt declines in seasonal precipitation leading to drought episodes since 1990s [32,34,45,46,76]. Meanwhile, R95 p shows large uncertainties over the study area during MAM season as compared to other indices, with larger interquartile model spread exhibited (Figure 4).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, many sub-regions have experienced notable changes in precipitation over the recent decades [4,21,26]. Similarly, positive trajectories in temperature have been observed and are projected to increase significantly across the continent [20,[27][28][29][30][31][32]. This will affect the broader population's livelihoods that mainly rely on rainfed agriculture [33].…”
Section: Introductionmentioning
confidence: 99%
“…Studies, e.g., [35][36][37], have shown that climate change will still affect the socioeconomic development of less developed countries due to their dependence on climatic conditions even under low emission scenarios. Researchers have also indicated that East Africa has experienced a reduction in Interannual rainfall variability and a quick rise in surface air temperature (SAT), which may further intensify the drought conditions over the region [38,39]. A recent study [40] indicates that rainfall highly fluctuates in the short rainy season during October to November (OND) than the long rainy season of March to May (MAM).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the research on GCMs has made great progress, and the coupled model intercomparison project has been developed to the sixth stage (CMIP6) (Kim et al 2020;Xu et al 2021). The CMIP6 adds special test designs that are closer to actual physical and biogeochemical processes from the perspective of how to assess future climate change (Ayugi et al 2021;Srivastava et al 2020;Yazdandoost et al 2021). Therefore, the CMIP6 can carry out more numerical experiments according to the new numerical experiment design scheme, thereby continuing to improve the resolution of the models (Mondal et al 2021;Rivera and Arnould 2020;Shafeeque and Luo 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Hanjiang River Basin (HRB) is located in the climate transition zone between China's north and south, and it is more sensitive and susceptible to climate change (Mohanty and Simonovic 2021;Yazdandoost et al 2021;Zhu and Yang 2020). The analysis of the changes in the spatio-temporal distribution characteristics of water resources in the HRB under future climate change is conducive to coping with the uncertain challenges brought by climate change (Ayugi et al 2021;Mondal et al 2021). Affected by the rapid economic and social development, the demand for water resources in the HRB has grown rapidly (Rivera and Arnould 2020;Shafeeque and Luo 2021;Wang et al 2021).…”
Section: Introductionmentioning
confidence: 99%